A global biodiversity fund to implement distributive justice for genetic resources. Issue 4 (15th May 2019) - Deplazes‐Zemp, Anna
Abstract: This article examines the question of who has a right to control and benefit from genetic resources globally. To this end it draws on different accounts in the resource rights literature with a focus on the specific features that distinguish genetic resources from other types of natural resources. It will be argued that due to the intangible and non‐territorial nature of genetic resources, territorial rights over these resources are difficult to maintain. Moreover, the vulnerability of genetic resources implies that much cost and effort is required to protect them. I will argue that not only benefits resulting from the use of genetic resources but also these costs associated with their protection should be an object of distributive justice. To accommodate these two points I will introduce the model of a global biodiversity fund that could replace the bilateral access and benefit sharing negotiations suggested by the Convention on Biological Diversity.